Maximizing the functional lifetime of Protein A resins. (20th March 2017) - Zhang, Jennifer; Siva, Sethu; Caple, Ryan; Ghose, Sanchayita; Gronke, Rob
Abstract : Protein A chromatography is currently the industry gold‐standard for monoclonal antibody and Fc‐fusion protein purification. The high cost of Protein A, however, makes resin lifetime and resin reuse an important factor for process economics. Typical resin lifetime studies performed in the industry usually examine the effect of resin re‐use on binding capacity, yield, and product quality without answering the fundamental question of what is causing the decrease in performance. A two part mechanistic study was conducted in an attempt to decouple the effect of the two possible factors (resin hydrolysis and/or degradation vs. resin fouling) on column performance over lifetime of the most commonly used alkali‐stable Protein A resins (MabSelect SuRe and MabSelect SuRe LX). The change in binding capacity as a function of sodium hydroxide concentration (rate of hydrolysis), temperature, and stabilizing additives was examined. Additionally, resin extraction studies and product cycling studies were conducted to determine cleaning effectiveness (resin fouling) of various cleaning strategies. Sodium hydroxide‐based cleaning solutions were shown to be more effective at preventing resin fouling. Conversely, cold temperature and the use of stabilizing additives in conjunction with sodium hydroxide were found to be beneficial in minimizing the rate of Protein A ligand hydrolysis. An effective and robust cleaning strategy is presented here to maximize resin lifetime and thereby the number of column cycles for future manufacturing processes. © 2017 American Institute of Chemical Engineers Biotechnol. Prog., 33:708–715, 2017